PENGARUH KODE ETIK, MATERIALITAS AUDIT DAN RISIKO AUDIT TERHADAP OPINI AUDITOR - Cholifah Husti Laila; Novita Novita (UNIB Press, 2019)
This research aims to make case analyze the impact of business ethics, level of audit materiality and audit risk towards auditor opinion. For public accountant engaged in assurance services. The result expected to contribute to the audit process of the client's financial statements in order to improve the performance of public accountants and achieve the goals of public accountants. The respondents that used in this research are the public accountant who works in public accountant firms. Data was collected using a questionnaire. Method verification analysis was used to test hypothesis and structural modeling with Partial Least Square application that is SmartPLS 3rd version. Result of this research reveals that of the three variables; business ethics, audit materiality, and audit risk, only audit risk that does not have a significant effect on auditor opinion. Audit risk does not have a significant effect on auditor opinion because the public accountant feels a lot and complexity of the data that the auditor must examine and the component influences audit risk. Keywords: ethics, materiality, risk, auditor opinion.